DO EARNINGS MANAGEMENT ABLE TO REDUCE STICKINESS COST LEVELS? - Rani Media Martania; Nurafni Eltivia; Mohamad Arief Setiawan (Jurnal Reviu Akuntansi dan Keuangan, 2018)
The purpose of this research is to determine the occurence of stickiness cost in SG&A (Selling, General and Administration) cost and to see whether the stickiness cost degree can be derive through earning management. Multiple linear regression using regression model from Anderson et al. and Farzaneh et al. are carried out to analyze the data. The results of this research show that SG&A cost is sticky, because it increased by 0.908% at 1% increase in sales but decreased by 0.016% at 1% decrease in sales. It happens because the manager retain the unutilized resources when facing a decline in sales. Furthemore, the results of this research find that earning management can derive the degree of stickiness cost, even cause anti-sticky in SG&A cost. It happens because the manager who has an incentive to avoid reporting loses and earning decreases, try to reduce cost when sales decline by earning management.